2017
DOI: 10.1111/arcm.12328
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical and Petrographic Analysis of Late Bronze Age Cypriot Ceramics (White Slip I and II and Monochrome) from Tell Atchana/Alalakh (Hatay) in the Amuq Valley

Abstract: White Slip ware, both White Slip I and II, and Monochrome ware are Middle to Late Bronze Age Cypriot pottery types found across a large area of the Eastern Mediterranean region. A vast quantity of these wares has also been uncovered in Tell Atchana/ancient Alalakh in Hatay in southern Anatolia. We analysed a total of 56 White Slip (n = 36) and Monochrome potsherds (n = 20) from Tell Atchana using XRF, ICP-MS and petrographic thin-section methods. The main aim of the study was to explore the compositional chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…Given this potential effect, concerns have been raised regarding the impact of LED lighting on circadian rhythms, as stated in a recent USDOE fact sheet [39]. It suggested that chronic disruption of circadian rhythmicity by LED light sources has the potential to yield serious long-term health consequences, although there are no examples in any literature of such circadian disruption arising from the installation of LED public lighting [40].…”
Section: The Radiometric and Photometric Properties Of The Artificial...mentioning
confidence: 99%
“…Given this potential effect, concerns have been raised regarding the impact of LED lighting on circadian rhythms, as stated in a recent USDOE fact sheet [39]. It suggested that chronic disruption of circadian rhythmicity by LED light sources has the potential to yield serious long-term health consequences, although there are no examples in any literature of such circadian disruption arising from the installation of LED public lighting [40].…”
Section: The Radiometric and Photometric Properties Of The Artificial...mentioning
confidence: 99%